STRATEGI YANG TEPAT UNTUK MENGANTISIPASI PERKEMBANGAN FRINGE-SETTLEMENTS DI KA-WASAN RURAL-URBAN FRINGE BERDASARKAN MODEL KOMBINASI - Imma Widyawati Agustin; Hisashi Kubota (TATALOKA, 2012)
This research is used a combination model by the proportion of urban land use functions, residential properties and the proportion of agricultural land use. It was also calculated based on the distance bands. The objective of this research is to improve the policy of fringe-settlements development in the rural-urban fringe area. This result are: (1) There has been a conversion of productive agricultural-land into residential-land. (2) New fringe-settlements should be established in inner fringe. Outer fringe area should be keep for agricultural-land. Thus, there is a balance in the rural-urban fringe area. (3) An appropriate strategy for rural-urban fringe area is: Tax Defferal and Abatement Laws is suitable to be applied in the inner fringe area because the majority of the population in no longer committed to preserve agricultural and activities. Utility Extension Policy and Police Power Mechanism are suitable to be applied in the outer fringe area because the availability of agricultural land is still a lot and the farmer committed to agricultural land and agricultural activities.